Dynamics of DNA Origami Lattices - Julin, Sofia; Keller, Adrian; Linko, Veikko (Bioconjugate Chemistry)
Keywords: Organic Chemistry; Pharmaceutical Science; Pharmacology; Biomedical Engineering; Bioengineering; Biotechnology

Stiffness optimization and reliable design of a hip implant by using the potential of additive manufacturing processes - Risse, Lena; Woodcock, Steven Clifford; Brüggemann, Jan-Peter; Kullmer, Gunter; Richard, Hans Albert (BioMedical Engineering OnLine)
Abstract Background Due to the steadily increasing life expectancy of the population, the need for medical aids to maintain the previous quality of life is growing. The basis for independent mobility is a functional locomotor system. The hip joint can be so badly damaged by everyday wear or accelerated by illness that reconstruction by means of endoprostheses is necessary. Results In order to ensure a high quality of life for the patient after this procedure as well as a long service life of the prosthesis, a high-quality design is required, so that many different aspects have to be taken into account when developing prostheses. Long-term medical studies show that the service life and operational safety of a hip prosthesis by best possible adaptation of the stiffness to that of the bone can be increased. The use of additive manufacturing processes enables to specifically change the stiffness of implant structures. Conclusions Reduced implant stiffness leads to an increase in stress in the surrounding bone and thus to a reduction in bone resorption. Numerical methods are used to demonstrate this fact in the hip implant developed. The safety of use is nevertheless ensured by evaluating and taking into account the stresses that occur for critical load cases. These results are a promising basis to enable longer service life of prostheses in the future.
Keywords: Radiology; Nuclear Medicine and imaging; Biomedical Engineering; General Medicine; Biomaterials; Radiological and Ultrasound Technology

FeMn with Phases of a Degradable Ag Alloy for Residue-Free and Adapted Bioresorbability - Krüger, Jan Tobias; Hoyer, Kay-Peter; Huang, Jingyuan; Filor, Viviane; Mateus-Vargas, Rafael Hernan; Oltmanns, Hilke; Meißner, Jessica; Grundmeier, Guido; Schaper, Mirko (Journal of Functional Biomaterials)
The development of bioresorbable materials for temporary implantation enables progress in medical technology. Iron (Fe)-based degradable materials are biocompatible and exhibit good mechanical properties, but their degradation rate is low. Aside from alloying with Manganese (Mn), the creation of phases with high electrochemical potential such as silver (Ag) phases to cause the anodic dissolution of FeMn is promising. However, to enable residue-free dissolution, the Ag needs to be modified. This concern is addressed, as FeMn modified with a degradable Ag-Calcium-Lanthanum (AgCaLa) alloy is investigated. The electrochemical properties and the degradation behavior are determined via a static immersion test. The local differences in electrochemical potential increase the degradation rate (low pH values), and the formation of gaps around the Ag phases (neutral pH values) demonstrates the benefit of the strategy. Nevertheless, the formation of corrosion-inhibiting layers avoids an increased degradation rate under a neutral pH value. The complete bioresorption of the material is possible since the phases of the degradable AgCaLa alloy dissolve after the FeMn matrix. Cell viability tests reveal biocompatibility, and the antibacterial activity of the degradation supernatant is observed. Thus, FeMn modified with degradable AgCaLa phases is promising as a bioresorbable material if corrosion-inhibiting layers can be diminished.
Keywords: Biomedical Engineering; Biomaterials

Low Cycle Fatigue Performance of Additively Processed and Heat-Treated Ti-6Al-7Nb Alloy for Biomedical Applications - Hein, Maxwell; Kokalj, David; Lopes Dias, Nelson Filipe; Stangier, Dominic; Oltmanns, Hilke; Pramanik, Sudipta; Kietzmann, Manfred; Hoyer, Kay-Peter; Meißner, Jessica; Tillmann, Wolfgang; Schaper, Mirko (Metals)
In biomedical engineering, laser powder bed fusion is an advanced manufacturing technology, which enables, for example, the production of patient-customized implants with complex geometries. Ti-6Al-7Nb shows promising improvements, especially regarding biocompatibility, compared with other titanium alloys. The biocompatible features are investigated employing cytocompatibility and antibacterial examinations on Al2O3-blasted and untreated surfaces. The mechanical properties of additively manufactured Ti-6Al-7Nb are evaluated in as-built and heat-treated conditions. Recrystallization annealing (925 °C for 4 h), β annealing (1050 °C for 2 h), as well as stress relieving (600 °C for 4 h) are applied. For microstructural investigation, scanning and transmission electron microscopy are performed. The different microstructures and the mechanical properties are compared. Mechanical behavior is determined based on quasi-static tensile tests and strain-controlled low cycle fatigue tests with total strain amplitudes εA of 0.35%, 0.5%, and 0.8%. The as-built and stress-relieved conditions meet the mechanical demands for the tensile properties of the international standard ISO 5832-11. Based on the Coffin–Manson–Basquin relation, fatigue strength and ductility coefficients, as well as exponents, are determined to examine fatigue life for the different conditions. The stress-relieved condition exhibits, overall, the best properties regarding monotonic tensile and cyclic fatigue behavior.
Keywords: General Materials Science; Metals and Alloys; laser powder bed fusion; Ti-6Al-7Nb; titanium alloy; biomedical engineering; low cycle fatigue; microstructure; nanostructure

FeMn with Phases of a Degradable Ag Alloy for Residue-Free and Adapted Bioresorbability - Krüger, Jan Tobias; Hoyer, Kay-Peter; Huang, Jingyuan; Filor, Viviane; Mateus-Vargas, Rafael Hernan; Oltmanns, Hilke; Meißner, Jessica; Grundmeier, Guido; Schaper, Mirko (Journal of Functional Biomaterials)
The development of bioresorbable materials for temporary implantation enables progress in medical technology. Iron (Fe)-based degradable materials are biocompatible and exhibit good mechanical properties, but their degradation rate is low. Aside from alloying with Manganese (Mn), the creation of phases with high electrochemical potential such as silver (Ag) phases to cause the anodic dissolution of FeMn is promising. However, to enable residue-free dissolution, the Ag needs to be modified. This concern is addressed, as FeMn modified with a degradable Ag-Calcium-Lanthanum (AgCaLa) alloy is investigated. The electrochemical properties and the degradation behavior are determined via a static immersion test. The local differences in electrochemical potential increase the degradation rate (low pH values), and the formation of gaps around the Ag phases (neutral pH values) demonstrates the benefit of the strategy. Nevertheless, the formation of corrosion-inhibiting layers avoids an increased degradation rate under a neutral pH value. The complete bioresorption of the material is possible since the phases of the degradable AgCaLa alloy dissolve after the FeMn matrix. Cell viability tests reveal biocompatibility, and the antibacterial activity of the degradation supernatant is observed. Thus, FeMn modified with degradable AgCaLa phases is promising as a bioresorbable material if corrosion-inhibiting layers can be diminished.
Keywords: Biomedical Engineering; Biomaterials

FeMn with Phases of a Degradable Ag Alloy for Residue-Free and Adapted Bioresorbability - Krüger, Jan Tobias; Hoyer, Kay-Peter; Huang, Jingyuan; Filor, Viviane; Mateus-Vargas, Rafael Hernan; Oltmanns, Hilke; Meißner, Jessica; Grundmeier, Guido; Schaper, Mirko (Journal of Functional Biomaterials)
The development of bioresorbable materials for temporary implantation enables progress in medical technology. Iron (Fe)-based degradable materials are biocompatible and exhibit good mechanical properties, but their degradation rate is low. Aside from alloying with Manganese (Mn), the creation of phases with high electrochemical potential such as silver (Ag) phases to cause the anodic dissolution of FeMn is promising. However, to enable residue-free dissolution, the Ag needs to be modified. This concern is addressed, as FeMn modified with a degradable Ag-Calcium-Lanthanum (AgCaLa) alloy is investigated. The electrochemical properties and the degradation behavior are determined via a static immersion test. The local differences in electrochemical potential increase the degradation rate (low pH values), and the formation of gaps around the Ag phases (neutral pH values) demonstrates the benefit of the strategy. Nevertheless, the formation of corrosion-inhibiting layers avoids an increased degradation rate under a neutral pH value. The complete bioresorption of the material is possible since the phases of the degradable AgCaLa alloy dissolve after the FeMn matrix. Cell viability tests reveal biocompatibility, and the antibacterial activity of the degradation supernatant is observed. Thus, FeMn modified with degradable AgCaLa phases is promising as a bioresorbable material if corrosion-inhibiting layers can be diminished.
Keywords: Biomedical Engineering; Biomaterials

Additively processed TiAl6Nb7 alloy for biomedical applications - Hein, Maxwell; Hoyer, Kay-Peter; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)
Laser beam melting (LBM) is an advanced manufacturing technology providing special features and the possibility to produce complex and individual parts directly from a CAD model. TiAl6V4 is the most common used titanium alloy particularly in biomedical applications. TiAl6Nb7 shows promising improvements especially regarding biocompatible properties due to the substitution of the hazardous vanadium. This work focuses on the examination of laser beam melted TiAl6Nb7. For microstructural investigation scanning electron microscopy including energydispersive x-ray spectroscopy as well as electron backscatter diffraction are utilized. The laser beam melted related acicular microstructure as well as the corresponding mechanical properties, which are determined by hardness measurements and tensile tests, are investigated. The laser beam melted alloy meets, except of breaking elongation A, the mechanical demands like ultimate tensile strength Rm, yield strength Rp0.2, Vickers hardness HV of international standard ISO 5832-11. Next steps contain comparison between TiAl6Nb7 and TiAl6V4 in different conditions. Further investigations aim at improving mechanical properties of TiAl6Nb7 by heat treatments and assessment of their influence on the microstructure as well as examination regarding the corrosive behavior in human bodylike conditions.
Keywords: Laser beam melting; titanium alloy; TiAl6Nb7; biomedical engineering; implants

Investigating the microstructure of an additively manufactured FeCo alloy: an electron microscopy study - Pramanik, Sudipta; Tasche, Lennart; Hoyer, Kay-Peter; Schaper, Mirko (Additive Manufacturing)
Keywords: Industrial and Manufacturing Engineering; Engineering (miscellaneous); General Materials Science; Biomedical Engineering

Encrypted polynomial control based on tailored two‐party computation - Schulze Darup, Moritz (International Journal of Robust and Nonlinear Control)
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering; Mechanical Engineering; Aerospace Engineering; Biomedical Engineering; General Chemical Engineering; Control and Systems Engineering

Optimal event‐triggered transmission scheduling for privacy‐preserving wireless state estimation - Lu, Jingyi; Leong, Alex S.; Quevedo, Daniel E. (International Journal of Robust and Nonlinear Control)
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering; Mechanical Engineering; Aerospace Engineering; Biomedical Engineering; General Chemical Engineering; Control and Systems Engineering

The influence of motor tasks and cut-off parameter selection on artifact subspace reconstruction in EEG recordings - Anders, Phillipp; Müller, Helen Martha; Skjæret-Maroni, Nina; Vereijken, Beatrix; Baumeister, Jochen (Medical & Biological Engineering & Computing)
Advances in EEG filtering algorithms enable analysis of EEG recorded during motor tasks. Although methods such as artifact subspace reconstruction (ASR) can remove transient artifacts automatically, there is virtually no knowledge about how the vigor of bodily movements affects ASRs performance and optimal cut-off parameter selection process. We compared the ratios of removed and reconstructed EEG recorded during a cognitive task, single-leg stance, and fast walking using ASR with 10 cut-off parameters versus visual inspection. Furthermore, we used the repeatability and dipolarity of independent components to assess their quality and an automatic classification tool to assess the number of brain-related independent components. The cut-off parameter equivalent to the ratio of EEG removed in manual cleaning was strictest for the walking task. The quality index of independent components, calculated using RELICA, reached a maximum plateau for cut-off parameters of 10 and higher across all tasks while dipolarity was largely unaffected. The number of independent components within each task remained constant, regardless of the cut-off parameter used. Surprisingly, ASR performed better in motor tasks compared with non-movement tasks. The quality index seemed to be more sensitive to changes induced by ASR compared to dipolarity. There was no benefit of using cut-off parameters less than 10.
Keywords: Computer Science Applications; Biomedical Engineering

Depth camera based statistical shape fitting approach for the creation of an individualized lower body biomechanical model: validity and reliability - Taetz, Bertram; Teufl, Wolfgang; Weidmann, Alexander; Pietschmann, Juliane; Jöllenbeck, Thomas; Bleser, Gabriele (Computer Methods in Biomechanics and Biomedical Engineering)
Keywords: Computer Science Applications; Human-Computer Interaction; Biomedical Engineering; General Medicine; Bioengineering

Hot isostatic pressing of IN718 components manufactured by selective laser melting - Tillmann, Wolfgang; Schaak, Christoph; Nellesen, J.; Schaper, Mirko; Aydinöz, Mehmet Esat; Hoyer, Kay-Peter (Additive Manufacturing)
Keywords: Industrial and Manufacturing Engineering; Engineering (miscellaneous); General Materials Science; Biomedical Engineering

Novel Self-Assembled Nanoparticles of Testosterone-Modified Glycol Chitosan and Fructose Chitosan for Controlled Release - Quiñones, Javier Pérez; Gothelf, Kurt V.; Kjems, Jørgen; Heras, Angeles; Schmidt, Claudia; Peniche, Carlos (Journal of Biomaterials and Tissue Engineering)
Keywords: Biomedical Engineering; Medicine (miscellaneous); Bioengineering; Biotechnology